PENYELESAIAN KASUS KORUPSI SECARA INFORMAL PADA PEMERINTAHAN NAGARI DI SUMATERA BARAT - Fitriati Fitriati; Sjafaruddin Tamin (Faculty of Law, Universitas Diponegoro, 2013)
The purpose of research is to analyze the settlement of cases of corruption in the government through informal villages. Approach to the problems that used descriptive-analytical. The collected data were analyzed using qualitative analysis to start with the literature used. In research found that this form of corruption in an informal settlement is through deliberation nagari, custom, direct action by the people in the form of social sanctions. The reason why the lines in formal chosen is because it is considered more effective and efficient in terms of time, procedures and costs.